A comparative study of minivac suction drain in Lichtenstein tension-free mesh inguinal hernioplasty at Basaweshwar teaching and general hospital, Kalaburagi, Karnataka - Nitin Kalaskar; Basavantrao C Patil; Vignesh M (Asian Journal of Medical Sciences, 2025)
Background: Despite the high prevalence of inguinal hernias worldwide, intraoperative drain placement remains a controversial topic. The benefit of reducing post-operative complications has not yet been clearly demonstrated. This study investigates whether a drain prevents post-operative complications after the Lichtenstein tension-free mesh hernioplasty technique. Aims and Objectives: The study is to compare minivac suction drain in Lichtenstein tension-free mesh hernioplasty in inguinal hernia repair at Basaweshwar teaching and general hospital, Gulbarga. To study the merits and demerits of minivac suction drain in inguinal hernia repairs. Materials and Methods: This study is a retrospective comparative study to compare 50 patients with inguinal hernia undergoing Lichtenstein tension-free mesh hernioplasty over a period of 2 years. Patients were randomized into two groups, one group containing 25 patients with a minivac drain and one group containing 25 patients without a drain. Results were compared in two groups for hematoma, seroma, wound infection, pain, and duration of hospital stay. Results: From the study, it is concluded that keeping a drain in Lichtenstein tension-free mesh hernioplasty is beneficial in complications associated with Seroma and Hematoma formation and reduction in hospital stay, but no significant difference in pain post-surgery. In our study, three patients in the drain group had wound infection, whereas in the non-drain group six patients had infection, but it was not statistically significant. At the end of the study, we can conclude that the patients with a drain benefited in the form of less chances of seroma and hematoma. Conclusion: From the study, it is concluded that the use of suction drain in Lichtenstein tension-free mesh hernioplasty is beneficial in complications associated with Seroma and Hematoma formation and reduction in hospital stay, but no significant difference in post-operative pain.